The Future of Self-Service Technologies: Understanding User Intentions in Guyana - Dave Sarran (Ali Institute or Research and Publication, 2025)
Self-service technologies (SSTs) are playing a crucial role in the advancement of both developed and developing economies. These technologies, including automated teller machines (ATMs) and self-service kiosks, offer organizations more accessibility and efficiency. However, the successful implementation and deployment of SSTs, particularly in developing countries, is a complex and demanding task. Understanding the determinants of their adoption is therefore crucial. This study examines the determinants of citizens' willingness to utilize self-service technology, focusing specifically on self-service kiosks in Guyana. This study develops a conceptual model extending TAM with three additional predictor variables: Resistance to Change, Technology Anxiety, and User Interface. The data were collected through an online survey from 350 Guyanese citizens, and Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed for testing and validating the model. The findings indicate that Resistance to Change, Technology Anxiety, and User Interface have significant impacts on Perceived Ease of Use. Additionally, Technology Anxiety was identified as a predictor of Resistance to Change. Perceived Ease of Use was a significant predictor of Perceived Usefulness, and Perceived Usefulness and Perceived Ease of Use were significant predictors of Attitude Toward Use. Finally, Attitude Toward Use was a predictor of intention to use self-service kiosks. By providing insights into the determinants of citizens' uptake of self-service technology in Guyana, the current study provides valuable suggestions for practitioners on how to design and implement successful public self-service systems.